Power and Changing Riverscapes: The Socioecological Fix and Newspaper Discourse Concerning the Rhône River (France) Since 1945. Issue 6 (2nd November 2019) - Comby, Emeline; Le Lay, Yves-François; Piégay, Hervé
Abstract : Riverscapes are constructs that mix natural components with political, socioeconomic, and technical strategies. This article shows how the riverscapes of the Rhône in France have changed under the influence of different power relations. We use newspapers to highlight the potential of news outlets as a data source with which to apply Foucault's critical and genealogical methods and to develop a political ecology of socioecological fixes. Media coverage is proxied by a content analysis and textual data analysis of 1, 079 articles published in Le Monde from 1945 to 2013. We study variations of newspaper discourse to create five chronological narratives: (1) the reconstruction of France and the creation of new landscapes, (2) the promotion of national development through navigation, (3) the quest for energy independence through dams and nuclear power plants, (4) the abandonment of major projects, and (5) the definition of pollution and flooding as national problems at the same time as the rediscovery of landscapes as local amenities. River landscapes are related to national political objectives, even though schemes for the Rhône seem to be ever less geared to national ambitions. In specific contexts, bottom-up advocacy coalitions occasionally prove powerful enough to influence socioecological trajectories: Their power seems to be on the rise as the national project wanes. They are often opposed to new socioecological fixes. Although political drivers are instrumental in shaping the Rhône, economic dynamics are crucial. Energy production seems to be a good indicator for monitoring socioecological fixes along major rivers because it involves fixed capital. Key Words: construction of riverscape, discourse, political ecology, socioecological fix, temporal patterns.